Nephrotic Syndrome Due to Primary Renal Disease in Adults: II. A Controlled Trial of Prednisolone and Azathioprine. Issue 5656 (31st May 1969) - Sharpstone, P.; Ogg, C. S.; Cameron, J. S.
Abstract : A controlled trial in 20 adult patients with the nephrotic syndrome due to proliferative glomerulonephritis compared the effects of consecutive eight-week courses of treatment with prednisolone in conventional dosage and a low-dose azathioprine–prednisolone combination. Though the azathioprine regimen avoided serious toxicity and produced a statistically significant improvement in creatinine clearance and urine protein excretion, the results were not significantly better than with prednisolone itself and overall were not of great clinical value. Prolongation of the azathioprine–prednisolone treatment to one year was associated with some small improvement in the results. The effectiveness of prednisolone in the nephritic syndrome of adults with minimal renal histological abnormality was confirmed by a complete loss of proteinuria within eight weeks in six out of eight patients and substantial reduction in the other two. These two patients subsequently received azathioprine as well but with equivocal results.